2020
DOI: 10.1097/ftd.0000000000000733
|View full text |Cite
|
Sign up to set email alerts
|

A High Plasma Lamotrigine Concentration at Week 2 as a Risk Factor for Lamotrigine-Related Rash

Abstract: Background: Reportedly, a high plasma concentration of lamotrigine plays a role in the development of lamotrigine-related rash. The relationship between plasma concentrations of lamotrigine at week 2 and the lamotrigine-related rash was prospectively studied in 84 patients (22 males and 62 females) with treatment-resistant depressive disorder during an 8-week treatment of lamotrigine augmentation. Methods: Eighty-four depressed patients with an insuffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Previous studies have reported that very slow titration schedules prevented the recurrence of rashes during rechallenge after the first occurrence of a LTG-induced rash 15 and that low plasma LTG concentration 2 weeks after initiation was associated with a low risk of rash. 16 The results of this study are consistent with those of previous studies regarding the risk of LTG-induced rash development in patients with epilepsy. Concomitant use of VPA 3,5,11 and female sex 5,17 have been reported to increase the risk of developing LTG-induced rashes.…”
Section: Safety and Titration Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies have reported that very slow titration schedules prevented the recurrence of rashes during rechallenge after the first occurrence of a LTG-induced rash 15 and that low plasma LTG concentration 2 weeks after initiation was associated with a low risk of rash. 16 The results of this study are consistent with those of previous studies regarding the risk of LTG-induced rash development in patients with epilepsy. Concomitant use of VPA 3,5,11 and female sex 5,17 have been reported to increase the risk of developing LTG-induced rashes.…”
Section: Safety and Titration Methodssupporting
confidence: 92%
“…Although the small sample size in the fast titration group might have affected accurate estimation, fast titration significantly increased the risk of rash development and slow titration significantly decreased this risk, suggesting that slow titration during the initiation of LTG reduces the risk of rash development in patients with mood disorders. Previous studies have reported that very slow titration schedules prevented the recurrence of rashes during rechallenge after the first occurrence of a LTG-induced rash 15 and that low plasma LTG concentration 2 weeks after initiation was associated with a low risk of rash 16 …”
Section: Discussionmentioning
confidence: 99%
“…Skin rash is the prevalent adverse reaction of LAM that mostly results in the withdrawal of LAM. A recent study showed a high mean plasma concentration (4.38 ± 1.23 μmol/L) at week 2 as a risk factor for LAM-related rash 28 . Usual risk factors for developing a LAM-related rash are: rapid titration, high LAM starting dose, history of rash after another antiepileptic drug, and simultaneous valproate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed a high mean plasma concentration (4.38 ± 1.23 μmol/L) at week 2 as a risk factor for LAM-related rash. 28 Usual risk factors for developing a LAM-related rash are: rapid titration, high LAM starting dose, history of rash after another antiepileptic drug, and simultaneous valproate treatment. In addition, the frequency of severe rashes with LAM such as Steven-Johnson syndrome and toxic epidermal necrolysis had a dramatic decline with the initiation of a step-bystep titration schedule in 1994.…”
Section: Discussionmentioning
confidence: 99%